TOK channels use the two gates in classical K+ channels to achieve outward rectification. Issue 7 (10th June 2020) - Lewis, Anthony; McCrossan, Zoe A.; Manville, Rían W.; Popa, M. Oana; Cuello, Luis G.; Goldstein, Steve A. N.
Abstract: TOKs are outwardly rectifying K + channels in fungi with two pore‐loops and eight transmembrane spans. Here, we describe the TOKs from four pathogens that cause the majority of life‐threatening fungal infections in humans. These TOKs pass large currents only in the outward direction like the canonical isolate from Saccharomyces cerevisiae (ScTOK), and distinct from other K + channels. ScTOK, AfTOK1 ( Aspergillus fumigatus ), and H99TOK ( Cryptococcus neoformans grubii ) are K + ‐selective and pass current above the K + reversal potential. CaTOK ( Candida albicans ) and CnTOK ( Cryptococcus neoformans neoformans ) pass both K + and Na + and conduct above a reversal potential reflecting the mixed permeability of their selectivity filter. Mutations in CaTOK and ScTOK at sites homologous to those that open the internal gates in classical K + channels are shown to produce inward TOK currents. A favored model for outward rectification is proposed whereby the reversal potential determines ion occupancy, and thus, conductivity, of the selectivity filter gate that is coupled to an imperfectly restrictive internal gate, permitting the filter to sample ion concentrations on both sides of the membrane.